Rigidity spectrum of the long-period variations of the galactic cosmic ray intensity in different epochs of solar activity. (July 2015) - Iskra, K; Siluszyk, M; Alania, M
Abstract: We investigate character of correlations between the rigidity spectrum exponent γ of the 11-year variations of the Galactic Cosmic Ray (GCR) intensity and the exponent v of the Power Spectral Density (PSD) of the Interplanetary Magnetic Field (IMF) turbulence in period 1968-2012 using data of the IMF and carefully selected neutron monitors. We show that a clear inversely correlation between γ and v is observed when a resonance frequency range f1 -f2 of the IMF turbulence (using for calculation of v ), are determined taking into account changes of the solar wind velocity Vsw and strength B of the IMF versus solar activity. We assume that an essential contribution to the scattering of GCR particles in the heliosphere is setting up generally by the turbulence of By and Bz components of the IMF. Therefore, in this paper we use the exponents vy and vz of PSD of the By and Bz components of the IMF turbulence. Generally, both γ and v can be accepted as the essential proxies to study GCR propagation near earth orbit in heliosphere for the rigidity range of GCR particles to which neutron monitors and ground muon telescopes respond